Elevated levels of the reactive metabolite methylglyoxal recapitulate progression of type 2 dffiabetes - Moraru, Alexandra; Pfaff, Daniel; Fleming, Thomas; Nawroth, Peter Paul; Teleman, Aurelio A. (Cell metabolism, 2018)
Summary The molecular causes of type 2 diabetes (T2D) are not well understood. Both type 1 diabetes (T1D) and T2D are characterized by impaired insulin signaling and hyperglycemia. From analogy to T1D, insulin resistance and hyperglycemia are thought to also play causal roles in T2D. Recent clinical studies, however, found that T2D patients treated to maintain glycemia below the diabetes definition threshold (HbA1c < 6.5%) still develop diabetic complications. This suggests additional insulin- and glucose-independent mechanisms could be involved in T2D progression and/or initiation. T2D patients have elevated levels of the metabolite methylglyoxal (MG). We show here, using Drosophila glyoxalase 1 knockouts, that animals with elevated methylglyoxal recapitulate several core aspects of T2D: insulin resistance, obesity, and hyperglycemia. Thus elevated MG could constitute one root cause of T2D, suggesting that the molecular causes of elevated MG warrant further study.